Falling sex ratios and emerging evidence of sex-selective abortion in Nepal: evidence from nationally representative survey data - Mahesh Puri; Melanie Dawn Frost; Peter Richard Andrew Hinde (BMJ Open)
Objectives To quantify trends in changing sex ratios of births before and after the legalisation of abortion in Nepal. While sex-selective abortion is common in some Asian countries, it is not clear whether the legal status of abortion is associated with the prevalence of sex-selection when sex-selection is illegal. In this context, Nepal provides an interesting case study. Abortion was legalised in 2002 and prior to that, there was no evidence of sex-selective abortion. Changes in the sex ratio at birth since legalisation would suggest an association with legalisation, even though sex-selection is expressly prohibited.Design Analysis of data from four Demographic and Health Surveys, conducted in 1996, 2001, 2006 and 2011.Setting Nepal.Participants 31 842 women aged 15–49.Main outcome measure Conditional sex ratios (CSRs) were calculated, specifically the CSR for second-born children where the first-born was female. This CSR is where the evidence of sex-selective abortion will be most visible. CSRs were looked at over time to assess the impact of legalisation as well as for population sub-groups in order to identify characteristics of women using sex-selection.Results From 2007 to 2010, the CSR for second-order births where the first-born was a girl was found to be 742 girls per 1000 boys (95% CI 599 to 913). Prior to legalisation of abortion (1998–2000), the same CSR was 1021 (906–1150). After legalisation, it dropped most among educated and richer women, especially in urban areas. Just 325 girls were born for every 1000 boys among the richest urban women.Conclusions The fall in CSRs witnessed post-legalisation indicates that sex-selective abortion is becoming more common. This change is very likely driven by both supply and demand factors. Falling fertility has intensified the need to bear a son sooner, while legal abortion services have reduced the costs and risks associated with obtaining an abortion.